GENDERED AND INTERGENERATIONAL RELATIONALITIES IN FUTURE ORIENTATIONS: GUATEMALAN SCHOOLCHILDREN’S REPORTS OF GENDER ROLES IN PRESENT AND FUTURE HOUSEHOLDS - Maupin, Jonathan N.; Hackman, Joseph (International Journal of Child, Youth and Family Studies, 2023)
This article examines children and youth’s future orientation in rural Guatemala by examining their reports of activities of adults and children in present and future households. A total of 690 students in a small town in highland Guatemala completed a household task attribution form that listed 29 tasks in seven domains (domestic chores, care for children, household decisions, responsibilities, household purchases, work for money, development) with four gendered household figures (man, woman, boy, girl). Using cultural consensus analysis, we analyze patterns of agreement and variation in responses to determine the existence of shared cultural models and gendered submodels in both time periods. Taking a gendered and intergenerational relationality perspective, we focus on the ways that future orientations reflect, (re)produce, and contest contemporary gender norms. Reports of task distributions in the present reflect “traditional” gender norms divided along “productive” and “reproductive” lines. While male participants’ conceptions of the future largely reproduced these structures, female participants appeared willing to increase their own domestic work to foster greater gender equality among their children.